Development of waqf in Indonesia: The SWOT analysis of Indonesia Waqf Board (BWI) - Haneef, Mohamed Aslam; Mustaffa Kamil, Nazrol Kamil; Ayuniyyah, Qurroh (2017)
Purpose – As the most Moslem populous country, Indonesia has a great potential in waqf assets and fund. The House of the Representatives has regulated Waqf Act No. 41/2004 as of 27 October 2004 to support the development of waqf in the country. Indonesia Waqf Board (abbreviated as BWI) was established by the President of the Republic of Indonesia as the implementation of this Act. The role is to become coordinating institution of existing nazhir (waqf managers) in managing and supervising waqf assets and fund. This paper aims to evaluate waqf management conducted by BWI. The paper also identifies the issues of waqf management in Indonesia by using SWOT (strengths, weaknesses, opportunities, and threats) analysis. Design/Methodology/Approach – The study employs both primary and secondary sources. The primary data is through the interview with the Vice Chairman of BWI, while secondary sources are through published regulation and reports, journal papers, and articles. Findings – Since its establishment, BWI has faced several strengths, weaknesses, opportunities, and weaknesses. The strengths include an independent status of BWI and good cooperation with other interrelated institutions. With regard to its weakness, the dualism between BWI and Waqf Directorate of Ministry of Religious Affair has been becoming further internal challenge for the Board. Moreover, lack of integration between BWI and other waqf institutions has also hampered BWI to achieve its objectives. The opportunities are the high Moslem population in Indonesia and great potential of waqf cash and land. On the other hand, the threats comprise lack of awareness and knowledge of the Moslem in Indonesia. Besides, the biggest threat occurs on the capacity of waqf managers (nazhir). Meanwhile, waqf land status, change in waqf land location, and controversy of cash waqf are considered as the other threats. Originality/value – This study is expected to provide the current condition in waqf management and its lesson learnt for the development of waqf in Indonesia, specifically, as well as in other countries, generally.